Heat Shock Protein 60 in Hepatocellular Carcinoma: Insights and Perspectives - Hoter, Abdullah; Rizk, Sandra; Naim, Hassan Y. (Frontiers in Molecular Biosciences, 2020)
Heat shock protein 60 (Hsp60) is a principal mitochondrial chaperone involved in myriad cellular processes and various malignancies. It plays a key role in mitochondrial protein folding and cellular protection against distinct stress factors. On the other hand, it supports cancer progression by interacting with oncogenic proteins and regulating tumor cell survival and proliferation. Therefore, targeting of HSP60 has been suggested as anti-cancer therapy. Despite its significance in several types of cancers, the role of HSP60 in hepatocellular carcinoma (HCC) has not been fully elucidated. In the present review, we discuss the multiple roles of HSP60 in HCC progression and its inhibition as a promising therapeutic tool for cancer treatment.